Peran Kepercayaan terhadap Pemerintah dalam Memoderasi Pengaruh Kesadaran Wajib Pajak dan Kualitas Pelayanan Fiskus terhadap Kepatuhan Wajib Pajak Orang Pribadi (Studi Kasus di KPP Pratama Depok Sawangan) - Paras Yustiani; Dani Rahman Hakim (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2026)
This study aims to determine the influence of taxpayer awareness and the quality of tax authority services on individual taxpayer compliance, with trust in the government serving as a moderating variable. This study employs a quantitative research design and utilizes primary data. The study population consists of all individual taxpayers registered at the KPP Pratama Depok Sawangan tax office. Based on the Slovin formula with a 10% margin of error, the minimum sample size required was 100 respondents; however, data from 118 respondents were successfully collected and processed using the incidental sampling technique. Data collection was conducted via questionnaires. The data analysis technique employed was Partial Least Squares-based Structural Equation Modeling (SEM-PLS), utilizing SmartPLS version 4 software. The results indicate that taxpayer awareness and the quality of tax authority services have a direct, positive, and significant influence on individual taxpayer compliance. Furthermore, trust in the government moderates and strengthens the influence of the quality of tax authority services on individual taxpayer compliance.